Heterogeneity in euro area monetary policy transmission: results from a large multi-country BVAR model - Michael Scharnagl; Martin Mandler; Ute Volz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We study cross-country differences in monetary policy transmission across the large four euro area countries (France, Germany, Italy and Spain) using a large Bayesian vector autoregressive model with endogenous prior selection. Drawing both on the posterior distributions of the cross-country differences in impulse responses as well as on a battery of other tests we find real output to respond less negatively to a monetary policy tightening in Spain than in the other three countries while the price level decline is weaker in Germany. Bond yields rise stronger and more persistently in France and Germany than in Italy and Spain.
Keywords: C11; C54; E52; 330